Search for new technological methods of strengthening treatment of crankshafts - Anatoly Prokofyevich Babichev; Mikhail Egorovich Popov; Ahmad El Dakduki; Philip Andreyevich Pastukhov (Advanced Engineering Research, 2015)
The work objective is searching new methods of strengthening processing of the cranked shaft. Modern constructive and processing methods of increasing the durability of the engine cranked shaft are considered. Some features of the key processing methods - nitriding, riveting on, steel shot blasting of fillets - are identified. The main task of the constructive methods to increase strength -crankshaft shaping that provides a more uniform stress distribution on shaft volume - both in the stress concentration zones, and outside them is considered. The required design shapes of the shaft are determined experimentally. New installation diagrams for the strengthening and stabilizing vibrowave and shock-vibrating machining of the engine crankshafts are proposed. It is experimentally established that the shock-vibrating machining allows the following: uniform hardening of the surface layer of all part features; sharp edge finishing and rounding; smooth transitions; avoidance of non-rigid shaft distortion that takes place at the local rolling of large part fillets.